Metabolic pathway catalyzed by Vanin-1 pantetheinase plays a suppressive role in influenza virus replication in human alveolar epithelial A549 cells - Yamashita, Nobuko; Yashiro, Masato; Ogawa, Hirohito; Namba, Hikaru; Nosaka, Nobuyuki; Fujii, Yousuke; Morishima, Tsuneo; Tsukahara, Hirokazu; Yamada, Masao (Biochemical and biophysical research communications, 2017)
Our previous analysis of gene expression profiles in the peripheral blood from patients with influenza A (H1N1) pdm09 pneumonia revealed elevated transcription levels of the vanin-1 (vascular non-inflammatory molecule 1, VNN1) gene, which encodes an epithelial ectoenzyme with pantetheinase activity involved in recycling coenzyme A. Here, to elucidate the role of VNN1 in influenza A virus (IAV) H1N1 infection, we investigated the change of VNN1 expression in the context of IAV infection and the effects of its related substances, i.e., its direct substrate pantetheine and its two metabolites pantothenic acid and cysteamine on the replication of IAV in the human alveolar epithelial carcinoma cell line A549. The messenger RNA expression of VNN1 in A549 cells was significantly increased (by 4.9-fold) after IAV infection under an elevated concentration of pantetheine. Moreover, VNN1 mRNA levels were elevated by > 100-fold in response to pro-inflammatory cytokines, especially TNF-α and IL-1β. Pantetheine significantly reduced the IAV replication and IAV Matrix 1 (M1) mRNA levels when it was administered prior to and during infection. In addition, cysteamine treatment during IAV infection significantly reduced the viral replication and IAV M1 mRNA levels, whereas pantothenic acid did not. These findings suggest that the metabolic pathway catalyzed by VNN1 pantetheinase plays a suppressive role in IAV infection in the respiratory tract, especially in severe conditions under hypercytokinemia. •Vanin-1 pantetheinase is involved in suppression of influenza A virus replication.•Cysteamine plays a central role in the suppression of influenza replication.•The expression of vanin-1 mRNA in A549 cells is stimulated by TNF-α and IL-1β.